ناظم عبد الجليل دراسة تاثير اضافة العامل المنشط للسطح دوداكيل بنزين سلفونات الامونيوم التوأميه على مقاومة الانضغاط لخلطة أسمنتية ذات المعالجة الرطبة - عبد الجليلناظم (University of Thi-Qar Journal of Science, 2019)
In this study we focused on adding (Dodecyl Benzene Ammonium Sulphonate) and this adding was in form of different ratio of these additive to the matrix of Iraqi cement (Om Quasar factory for cement). The prepared samples was in form of cubic and evaluated as they were treated with moisture treatment. All the prepared samples had a proportion of 3/1) cement to sand) and in the form of cubes with aside (50 mm) long. The weight rate of (Dodecyl Benzene Ammonium Sulphonate) to the cement was (1%-8%). The obtained results showed that the cement mixture that had the weight rate of 2% at moisture curing is the best as it has good mechanical properties (compressive strength near to pure samples). Also this kind of surfactant have an opposite effect on mechanical properties and this effect is related to adding ratio and curing time. The effect of surfactant (Dodecyl Benzene Ammonium Sulphonate) works as plasticizer on cement matrix so the application range of used cement specially in oil well where these applications need flexible cement with high workability.